2003
DOI: 10.1080/14763140308522820
|View full text |Cite
|
Sign up to set email alerts
|

Skiing

Abstract: The purpose of the investigation was to study the relationship between thrust phase duration, ground reaction force, velocity increase after pole thrust and pole angles versus pole length during double poling in roller skiing. Seven male regional elite cross-country skiers volunteered as subjects for the study. The subjects performed a maximal double pole thrust on roller skis with each of the three different pole lengths: 'short', self-selected (normal) and 'long'. The short and long poles were 7.5 cm shorter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 7 publications
3
11
0
Order By: Relevance
“…Based on this consideration we propose the following hypotheses: (i) elite level cross country skiers choose pole lengths for double poling so as to minimize the energetic cost of skiing at race pace, and (ii) pole length affects the kinematics of double poling as expressed by distinct changes in the mechanics. In accordance with previous studies (Nilsson and colleagues 12 ) we expected longer poles to be associated with increased ground contact times, an increase in the propulsive impulse produced by the poles for each poling cycle, and a decrease in poling frequency.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…Based on this consideration we propose the following hypotheses: (i) elite level cross country skiers choose pole lengths for double poling so as to minimize the energetic cost of skiing at race pace, and (ii) pole length affects the kinematics of double poling as expressed by distinct changes in the mechanics. In accordance with previous studies (Nilsson and colleagues 12 ) we expected longer poles to be associated with increased ground contact times, an increase in the propulsive impulse produced by the poles for each poling cycle, and a decrease in poling frequency.…”
Section: Introductionsupporting
confidence: 91%
“…They further assumed that increasing pole length would lead to an increase in poling cycle duration and a decrease in poling cycle rate, and thus potentially to a decrease in propulsive impulse and speed over multiple poling cycles. 12 In order to gain insight into the trade-off between increased propulsive thrust and decreased poling frequency with increasing pole length, Hansen and Losnegard tested the effect of pole length on an 80 m all-out sprint. They observed that the shortest time for the 80 m sprint occurred with the longest poles provided, poles that were longer than the poles freely-selected by the athletes.…”
Section: Introductionmentioning
confidence: 99%
“…As a part of this development, cross-country-skiing research has put a large focus on the double-poling technique. Several studies have investigated technique-related aspects of the double-poling motion (Nilsson et al 2003, 2013; Lindinger and Holmberg 2011; Holmberg et al 2005). Others have analysed the physiological demands related to the double-poling technique (Mikkola et al 2013; Stöggl et al 2013), and it has been concluded that double poling is more economical than the diagonal stride technique in flat and moderately uphill terrain (Hoffman and Clifford 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The skier utilizes various techniques depending on the terrain, and adapts by modifying the relative contributions of the upper and lower extremities to propulsive force1, 2 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Forward propulsion during DP technique is characterized by higher pole forces mainly generated by the dynamic flexion-extension of the upper extremities, especially the elbow joint, with a very short ground contact period3 ) . Meanwhile, the lower extremities contribute to the application of body weight to pole forces1, 2, 4,5,6 ) . Thus, as the DP technique involves continuous symmetrical and synchronous motion of both upper and lower extremities, there is a lack of recovery period between strokes, which increases the fatigue accumulation rate4, 6 ) .…”
Section: Introductionmentioning
confidence: 99%